International tourism in Małopolskie Województwo: the present situation and prospects for development - Kurek, Włodzimierz; Pawlusiński, Robert (Turyzm/Tourism, 2009)
Małopolskie Województwo is one of the most popular tourist regions in Poland. Due to many attractions, long traditions of hosting tourists and well-developed accommodation facilities, Małopolskie Województwo has become the destination for a growing number of international tourists in recent years. Significant growth in incoming international tourism is found both in Kraków and in mountain areas. The objective of this paper is to present the state of development of incoming international tourism in Małopolskie Województwo.